An Analysis of the Human Geographic Evolution of Mount Emei, China - Fu, Yugang; Zhen, Kunfang; Yang, Chunxue (Khwopa Journal, 2024)
An ancient Chinese poet wrote: The moon of Emei Mountain is half a wheel of autumn, and its shadow enters the waters of the Pingqiang River. With its emerald green peaks and majestic atmosphere, Mount Emei is a world-class cultural heritage recognized by the world. From the perspective of geologists, it is a rich geological museum. It has preserved more than 400 million years of sedimentary records and recorded more than 800 million years of geological history. As a famous cultural mountain, Mount Emei also preserves a rich historical and cultural heritage. In this paper, from the perspective of human geography, we adopt the literature analysis method to sort out the human history of Mount Emei. It explores the cultural genes and cultural changes of this famous mountain. It is found that Emei Mountain, as a mountain range with rich cultural precipitation, has been indelible in traditional Chinese culture and is of great significance to Chinese culture.